1995
DOI: 10.1038/ki.1995.13
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the repair process of experimental proliferative glomerulonephritis

Abstract: The recovery from the proliferative glomerulonephritis (GN) with reduction of hypercellularity is known in various experimental and human GN. To elucidate the participation of apoptosis in GN, we studied the experimental Thy-1.1 GN for six weeks. Apoptosis was recognized by both light and electron microscopy, and the biochemical expression of apoptosis was morphologically confirmed by in situ end-labeling method of fragmented DNA, using terminal deoxy-transferase. Mesangioproliferative GN was induced by a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 25 publications
3
129
0
Order By: Relevance
“…In this report, we demonstrated that the PI3-kinase-Akt pathway acts as a survival (anti-apoptotic) signal and that PDGF activates that pathway in mesangial cells. While PDGF has been reported to mediate the proliferation that deeply involved in the mesangial proliferation of Thy 1.1 nephritis and IgA nephritis (17)(18)(19), our data suggest that PDGF serves a separate function as a survival factor acting through the PI3-kinase-Akt pathway in glomerulonephritis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this report, we demonstrated that the PI3-kinase-Akt pathway acts as a survival (anti-apoptotic) signal and that PDGF activates that pathway in mesangial cells. While PDGF has been reported to mediate the proliferation that deeply involved in the mesangial proliferation of Thy 1.1 nephritis and IgA nephritis (17)(18)(19), our data suggest that PDGF serves a separate function as a survival factor acting through the PI3-kinase-Akt pathway in glomerulonephritis.…”
Section: Discussionmentioning
confidence: 68%
“…While morphologic evidence of mesangial apoptosis was observed in rat Thy1.1 glomerulonephritis (17)(18)(19), the regulation and function of the PI3-kinase-Akt pathway in mesangial cells has not been fully demonstrated under in vitro or in vivo conditions. To explore the role of the PI3-kinase-Akt pathway, we investigated the regulation of the Akt pathway in cultured mesangial cells in the present study.…”
mentioning
confidence: 99%
“…Single injection with the complement-fixing antibody to Thy1 antigen present on the mesangial-cell membrane causes acute mesangialcell loss and matrix dissolution, leading to ballooning of glomerular capillaries, formation of microaneurysms and loss of endothelial cells, followed by a repair phase that is characterized by mesangial and endothelial cell migration and proliferation, apoptosis, and matrix expansion. 5,20,29,30 In our WR BM 3 BN hematopoietic chimeras we demonstrated that anti-Thy1.1-induced glomerular injury was associated with a significant influx of bonemarrow-derived cells. Immunofluorescent double-staining with cell-specific markers revealed that these donor-derived cells included not only monocytes and macrophages, as expected, but also endothelial and mesangial cells, which were fully integrated into the glomerular structure and remained present after restoration of glomerular architecture had occurred.…”
Section: Discussionmentioning
confidence: 85%
“…Programmed cell death, a normal event in renal tissue homeostasis [1], has been considered a major mechanism for resolution of glomerular hypercellularity in glomerulonephritis [2,3], but also for loss of cellularity and scarring in chronic renal disease [1,4]. This is suggested by the enhanced apoptosis rate detected in human and experimental renal diseases [5], including diabetic nephropathy [6][7][8], and by its correlation with loss of renal function and structure [5].…”
Section: Introductionmentioning
confidence: 91%